Psychophysiological and subjective effects of cigarettes having varying nicotine yields but relatively constant "tar' yields - Pritchard, W S; Robinson, J H; Guy, T D; Davis, R A; Stiles, M F (Neuropsychobiology, 1996)
Thirty-two subjects were tested in five double-blind sessions-16 subjects in the morning (a.m.) following overnight smoking abstention, and 16 in the afternoon (p.m.) following ad lib smoking. In each session, subjects smoked 1 of 5 cigarettes having the following FTC nicotine/'tar' yields in mg: 0.08/8.5, 0.17/9.1, 0.37/9.8, 0.48/9.8, and 0.74/10.4. On a pre- to postsmoking basis, blood nicotine and heart rate increased with nicotine yield. The effect of nicotine yield on changes in self-rated anxiety was an inverted-U function, but this effect was possibly confounded by baseline differences. The following effects on EEG spectral-band magnitude were also obtained: (1) nicotine yields > or = 0.17 mg decreased delta; (2) nicotine yields of 0.37 and 0.48 mg decreased theta in a.m. subjects; (3) nicotine yields > or = 0.37 mg decreased alpha, the effect being greater in a.m. subjects; (4) no effect of yield on beta 1 was obtained; (5) nicotine yields of 0.48 and 0.74 mg increased the Cz-minus-T5 differential in beta 2. Pre- to postsmoking changes in this measure of beta 2 were not correlated with either blood nicotine or anxiety.